Microsoft SharePoint 2010 Building Solutions for SharePoint 2010 - Malik, Sahil; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
This book provides a fresh take on Microsoft$1 (Bs premier collaboration solution. A critical resource if you$1 (Bre developing on the SharePoint platform, this book features a complete focus on the new features and capabilities of SharePoint 2010. Through a thorough treatment of sites, web parts, data management, portal solutions, and business intelligence capabilities, you$1 (Bll appreciate author Sahil Malik$1 (Bs concise yet highly readable text. With this book, you$1 (Bll gain intermediate-level guidance for designing and deploying exciting business solutions based on Microsoft SharePoint 2010.s
The First Chapter. Please read! -- SharePoint Basics -- The SharePoint 2010 Feature Solution Framework -- WebParts and SharePoint Pages -- Client Object Model, ADO.NET Services, and Custom Services -- Managing SharePoint Data: Part 1 -- Managing SharePoint Data: Part 2 -- Enterprise Content Management -- Business Connectivity Services -- Workflows -- Business Intelligence -- Security.
Keywords: Computer science; Computer Science; Programming Techniques